A research on the influence of sewing machine parameters on seam puckering of thin coated fabric - Nguyen, Thanh Yến Xuân (Journal of Technical Education Science, 2011)
This article aims to explore the nature and causes of the phenomenon of seam pucker and remedial measures to products coated fabric used for children,s apparel jackets